Ganando grados de libertad: El manejo de la política monetaria en LATAM-5 - Emiliano Basco; Sebastián Katz; Luis Libonatti (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2023)
– By examining the reaction functions of the Central Banks of Brazil, Chile, Colombia, Mexico, and Peru (LATAM-5) over the period 2002-2019, this article explores the degree to which the adoption of inflation targeting regimes allowed these economies to have greater room of manouvre in conducting their monetary policy. On the one hand, we find that policy rates respond more than proportionally to deviations in expected inflation over a one-year horizon. On the other hand, we find that monetary policy can respond countercyclically to fluctuations in GDP. However, our results also show that some of these Central Banks are not entirely indifferent to the behavior of variables beyond those postulated in conventional Taylor rules. We find evidence that in most cases, monetary authorities respond positively and systematically to movements in the policy rate of the FED. Is this regularity indicative of restricted monetary autonomy in LATAM-5? Or, on the contrary, is this behavior compatible with the prescriptions of an optimal monetary policy rule for a small and open economy? To distinguish between these alternatives, we estimate a Vector Autoregressive (VAR) model for each of these economies. This allows us to analyze the response of monetary policy to different shocks and the transmission mechanisms to key macroeconomic variables, as well as its interaction with the FED's interest rate. Finally, our estimates shed light on how these Central Banks, utilizing the hard-earned greater degrees of freedom, responded to the episode of inflationary pressure following the pandemic.
Keywords: E52; E58; 330; Schock; Inflationssteuerung; Geldpolitik; VAR-Modell; Brasilien; Chile; Kolumbien; Mexiko; Peru